2010
DOI: 10.1093/cercor/bhp309
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin Sulfate Acts in Concert with Semaphorin 3A to Guide Tangential Migration of Cortical Interneurons in the Ventral Telencephalon

Abstract: Chondroitin sulfate (CS) carrying proteoglycans (PGs) are widely expressed in the nervous system, and there is increasing evidence that they regulate developmental mechanisms like neurite outgrowth, axonal guidance and neuronal migration. Moreover, they can also act indirectly by organizing and/or modulating growth factors and guidance molecules. We found that chondroitin-4-sulfate is coexpressed with semaphorin 3A (Sema 3A) in the striatal mantle zone (SMZ), a nontarget region of neuropilin (Nrp)-1-expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
59
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 78 publications
6
59
0
Order By: Relevance
“…1C) and the results of the in vitro assays described above demonstrated that the MGE-derived interneurons enter the deep migratory route. This is consistent with previous studies demonstrating that homotopically transplanted EGFP-explants from the VZ/SVZ of the MGE to the MGE of host slices migrate along the DMS and avoid entering the SMS in the MGE (Zimmer et al, 2008(Zimmer et al, , 2010aRudolph et al, 2010).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…1C) and the results of the in vitro assays described above demonstrated that the MGE-derived interneurons enter the deep migratory route. This is consistent with previous studies demonstrating that homotopically transplanted EGFP-explants from the VZ/SVZ of the MGE to the MGE of host slices migrate along the DMS and avoid entering the SMS in the MGE (Zimmer et al, 2008(Zimmer et al, , 2010aRudolph et al, 2010).…”
Section: Resultssupporting
confidence: 93%
“…The preferential migration of MGE-derived interneurons along the deep migratory stream is in concordance to what we found with homotopic grafting experiments reported in previous studies (Zimmer et al, 2008(Zimmer et al, , 2010aRudolph et al, 2010), as well as with the migration pattern shown by other groups, with DiIlabeled (Ghanem et al, 2007) or GFP-transfected MGE cells (Flames et al, 2004). EphA4, expressed in the SVZ of the ganglionic eminences, was recently reported to be involved in channeling MGE-derived interneurons into the deep migratory route by repulsive interactions with ephrinA5 and ephrinA3 expressed in the VZ and developing striatum, respectively (Zimmer et al, 2008;Rudolph et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Its presence affects synapse dynamics (15,17) and may influence plasticity in the mature CNS (22). An interaction between CS and Sema3A has been previously reported in vitro in neuronal cell culture (25) and also by co-localization studies of CSPG and Sema3A during development in vivo (26). More recently, we have shown that Sema3A is concentrated around PNNs in the mature CNS and that it co-localizes with several components of the PNNs (1).…”
mentioning
confidence: 60%